A música integrada à sala de aula numa perspectiva de formação continuada para professores dos anos iniciais do ensino fundamental: redimensionamento a prática pedagógica. - Targas, Keila de Mello (Universidade Federal de São Carlos, 2003)
The aim of the study was to investigate which contributions a continuing education program in music, for Elementary School teachers, could offer. We intended to investigate if such a program could lead to new learning and reflections as part of their teaching process and pedagogical practice. In which way it makes possible a contact with te music by generalist teacher and how this can be important in a classroom`s everyday routine in terms of reorganizing the pedagogical practice. As specific goals, we tried to analise the progress of the teachers involved in the process related to the learnings obtained, to the development of new abilities, to the transformation of pedagogical practice, to the conquest of a diferentiated school space in which experimentation, share of experiences, readings and reflections were aspects taken into higher account. With this goal, a music workshop was designed and developed with teachers (City Hall schools). It lasted 23 weeks and intended making possible for the participants the aquisition of basic musical knowledge through the development of pratical activities. At the same time that musical games and plays were developed, there was also space for discussion of the activities, readings and reflections. These processes made possible for the teachers to experience new alternatives for teaching music in the classroom, including inovating and adapting educacional practices, based on the experiences lived on the workshop, as well as applying these inovations in the classroom and reflection on this process. Regarding the proposed research question the results (of intervention and research)we could observe that the participation in the program, made possible for the teachers to acquire new experiences, build up new knowledge, develop new abilities, learn to deal with the contents in different ways, increase their capacity of adapting, adequing, and inovating according to the necessities of the classroom, learn to reflect more frequently about their own pedagogical performances and redirect them based on these reflections. Is was also possible to observe that the student, when motivated by the teacher to get in contact with music through games and plays, develops capacities of audio and rithmic perception, vocal and body expression, as well as learn how to better interact and get organized in group. The program of continuing education was an important tool to the encouragement of new learnings by the teachers, to develop reflective practice, and for them to perceive in a new way music education.
Keywords: Música na educação; Formação continuada de professores; Reflexão docente; Educação musical; Aprendizagem profissional da docência; CIENCIAS HUMANAS::EDUCACAO